(untitled) (European Journal of Engineering Science and Technology, 2019)
flat glass has been used for many centuries in wall openings and windows. It allows light in and broadens the visual horizon while protecting from the environmental elements. It also features a good potential for energy savings during the lifetime of the building. The technological developments it benefited from, in the last decades, transformed common plate glass into a stronger material, with safer and more predictable failure and some degree of post breakage capacity; even pseudo-ductility. For this reason, at present day, glass is a structural material with established credits. This allows for new buildings with dematerialized contours: the glass skin buildings; which are taking over the set in modern cities. There are several types of glass façade buildings, depending on the system used to fix the glass to the main structure. Point Fixed Glass Façade Systems (PFGFS) feature advantage in terms of architectural expression allowing for greater transparency, since no mullions and frames are required for additional support, only discrete point fixing. The design codes for structural glass are still under development, and one of the aspects that need further attention is the behavior of PFGFS when subjected to seismic action. This aspect is of the essence in the sense that forensic analysis to past earthquake events showed that important damage has been observed to GFS due to the in-plane racking actions. This may have severe costs in terms of human losses and in terms of economic costs (repair and downtime). The present paper addresses this theme by presenting an overview of its key aspects, a review of past research, both analytical and experiment for PFGFS under seismic loads, design code provisions for different countries as well as recommendations for prediction of racking capacity of Point Fixed Glass Façade Systems. The work presented in this paper is established in the framework of the ongoing research project: GF Seismic (FCT POCI-01-0145-FEDER-032539).